2020
DOI: 10.3390/ijerph17030903
|View full text |Cite
|
Sign up to set email alerts
|

Gender Based Violence against Women in Sub-Saharan Africa: A Systematic Review and Meta-Analysis of Cross-Sectional Studies

Abstract: This study aimed to systematically review studies that examined the prevalence of gender based violence (GBV) that included intimate partner violence (IPV) and non-IPV among women in sub-Saharan Africa (SSA). This evidence is an important aspect to work towards achieving the Sustainable Development Goals (SDG’s) target of eliminating all forms of violence in SSA. The Preferred Reporting Items for Systematic reviews and Meta-Analysis (PRISMA) guidelines were followed. Ovid Medline, CINAHL, Cochrane Central, Emb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
140
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(185 citation statements)
references
References 90 publications
(80 reference statements)
12
140
2
1
Order By: Relevance
“…The ndings are in line with Wandera et al, who reported the highest rate of sexual violence in the Eastern region, followed by Western, Central, and Northern regions [6]. However, the results deviate from a recent meta-analysis that reported Northern Uganda having the highest rate of sexual violence (50%) within Sub-Saharan Africa [5]. Although the Northern region has a record of past civil wars that were characterised by the violation of human rights, including sexual abuse [27], our study found no signi cant chances of sexual violence among women in this region.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The ndings are in line with Wandera et al, who reported the highest rate of sexual violence in the Eastern region, followed by Western, Central, and Northern regions [6]. However, the results deviate from a recent meta-analysis that reported Northern Uganda having the highest rate of sexual violence (50%) within Sub-Saharan Africa [5]. Although the Northern region has a record of past civil wars that were characterised by the violation of human rights, including sexual abuse [27], our study found no signi cant chances of sexual violence among women in this region.…”
Section: Discussionsupporting
confidence: 69%
“…A recent meta-analysis by Muluneh et al reported the prevalence of sexual violence in sub-Saharan Africa to be 18.6%, with the East African region having a higher prevalence compared to other regions [5]. A previous study indicated that 25% of the ever-married women in Uganda experienced some form of sexual violence [6].…”
Section: Introductionmentioning
confidence: 99%
“…Prior research has shown that during emergencies and disasters like coronavirus, in which people are told to stay home, sexual activity will continue and increase. Consequently, the risks of intimate partner violence, rape and HIV acquisition will also rise [12,13]. The South African government reported over 87,000 cases of gender based violence reported across the country in the first week of the coronavirus lockdown [20].…”
Section: Benefits Of Continuation: Enabling Pregnant and Breastfeedinmentioning
confidence: 99%
“…We decided to remain open to PrEP retention visits, when the participant was not able to attend prior to site closing. However, we know that during emergencies and disasters like coronavirus, in which people are told to stay home, sex will continue or increase, and risks of intimate partner violence and rape increase [12,13].…”
mentioning
confidence: 99%
“…Participants in Uganda were selected from poor urban communities in and around Kampala, with HIV prevalence of around 6.9% [26]. Both settings had high background rates of violence against women and girls, which may have contributed to a disproportionately higher HIV infection among women [27,28].…”
Section: Study Settingsmentioning
confidence: 99%